Residential status and household wealth disparities in modern contraceptives use among women in Ghana: a cross-sectional analysis - Anthony Mwinilanaa Tampah-Naah; Elijah Yendaw; Joshua Sumankuuro (BMC, 2023)
Abstract Background Modern contraceptive refers to "a product or medical procedure that interferes with reproduction from acts of sexual intercourse". The aim of this study was to assess the relationship between residential status and wealth quintile, and modern contraceptive use among women in Ghana. Methods We examined residential status and wealth quintile on contraceptive use analysing the 2006, 2011 and 2018 Multiple Indicator Cluster Surveys datasets. A sample of 30,665 women in their reproductive ages (15-49 years) were enrolled in the surveys across Ghana. STATA version 13 was used to process and analyse the data. It examined socioeconomic and demographic characteristics, assessed modern contraceptive use prevalence among women, and used logistic regression models to determine predictors. The results were presented in odds ratio and adjusted odds ratio with 95% confidence intervals. All statistical tests were measured with p < 0.05. Results In the three survey years, the highest prevalence of modern contraceptive usage was observed in 2011 (27.16%). The odds of using modern contraceptive increased by 19% in rural places (AOR = 1.19; 95% CI = 1.097-1.284) compared to urban places. The likelihood of women in second (AOR = 1.17; 95% CI = 1.065-1.289), middle (AOR = 1.24; 95% CI = 1.118-1.385), and fourth (AOR = 1.25; 95% CI = 1.113-1.403) wealth quintile using contraceptives increased compared to those of low wealth quintile. With the interactive terms, rural-second (AOR = 1.38; 95% CI = 1.042-1.830), rural-middle (AOR = 1.45; 95% CI = 1.084-1.933), rural-fourth (AOR = 1.52; 95% CI = 1.128-2.059), and rural-high (AOR = 1.42; 95% CI = 1.019-1.973) were more likely to use contraceptives compared to urban-low women. Despite lower odds, women of the age groups 20-24 (AOR = 2.33; 95% CI = 2.054-2.637), cohabitaing (AOR = 1.07; 95% CI = 0.981-1.173), secondary or higher education (AOR = 1.55; 95% CI = 1.385-1.736), Central (AOR = 1.48; 95% CI = 1.296-1.682) and Eastern (AOR = 1.48; 95% CI = 1.289-1.695) regions significantly predicted modern contraceptive use. Conclusion Modern contraceptive use in Ghana is low. Women in rural-rich categories are more likely to use modern contraceptives. Background factors such as age, marital status, educational attainment, and previous child experiences predict modern contraceptive use. It is recommended for the intensification of contraceptive awareness and utilization for all reproductive age women, regardless of education, marriage, or wealth.